Analysis of differences in knowledge of dental students in West Sumatra regarding dental photography: Analisis perbedaan pengetahuan mahasiswa profesi dokter gigi di sumatera barat mengenai fotografi dental - Putri, Violeta Audia; Surya, Leny Sang; Darmawangsa (Makassar Dental Journal PDGI Makassar, 2025)
Dental photography is one of the advances in digital digital technology in the field of dental photography which functions as a communication tool between dentists and patients used to help make a diagnosis. This study aimed to determine the differen-ces in knowledge of dental professional students in West Sumatra regarding dental photography. This quantitative study used a cross sectional design with 120 respondents from the Faculty of Dentistry, Baiturrahmah University and Andalas University and the sample was selected by simple random sampling. Data were collected through an online questionnaire (google form) with 14 knowledge questions. The results showed that most students had a good understanding of dental photography. The Baiturrah-mah had 38 students (63.3%) who recorded good knowledge. While at Andalas University there were 37 students (61.7%). It was concluded that there was no significant level of knowledge between students from the two universities (p-value=0.850) indicating that both groups had the same level of understanding.